2016
DOI: 10.1037/dev0000184
|View full text |Cite
|
Sign up to set email alerts
|

Phonological skills, visual attention span, and visual stress in developmental dyslexia.

Abstract: In this study, we concurrently investigated 3 possible causes of dyslexia-a phonological deficit, visual stress, and a reduced visual attention span-in a large population of 164 dyslexic and 118 control French children, aged between 8 and 13 years old. We found that most dyslexic children showed a phonological deficit, either in terms of response accuracy (92.1% of the sample), speed (84.8%), or both (79.3%). Deficits in visual attention span, as measured by partial report ability, affected 28.1% of dyslexic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 62 publications
7
108
2
6
Order By: Relevance
“…Samar and colleagues (Samar & Parasnis, ; Samar et al., ) suggested that all struggling deaf readers could be thought of as dyslexic on the basis of these visual deficits; thus, dyslexia may be the largest secondary disability in the deaf population. However, the role of these and other visual deficits (e.g., visual attention span, visual tracking) in dyslexia among the hearing population is controversial; although they frequently co‐occur, whether they are part of the underlying cause of dyslexia remains unclear (Hulme & Snowling, ; Saksida et al., ; Vellutino et al., ).…”
Section: Comparing Deaf Children and Hearing Children With Dyslexiamentioning
confidence: 99%
See 1 more Smart Citation
“…Samar and colleagues (Samar & Parasnis, ; Samar et al., ) suggested that all struggling deaf readers could be thought of as dyslexic on the basis of these visual deficits; thus, dyslexia may be the largest secondary disability in the deaf population. However, the role of these and other visual deficits (e.g., visual attention span, visual tracking) in dyslexia among the hearing population is controversial; although they frequently co‐occur, whether they are part of the underlying cause of dyslexia remains unclear (Hulme & Snowling, ; Saksida et al., ; Vellutino et al., ).…”
Section: Comparing Deaf Children and Hearing Children With Dyslexiamentioning
confidence: 99%
“…D yslexia and accompanying deficits have been widely researched (Bishop & Snowling, 2004;Lyon, Shaywitz, & Shaywitz, 2003;Peterson & Pennington, 2015;Ramus, 2003;Saksida et al, 2016;Snowling, 2000Snowling, , 2008Vellutino, Fletcher, Snowling, & Scanlon, 2004). With increasing awareness of dyslexia, a diagnosis of dyslexia in the United Kingdom can lead to recognition of children's needs and the provision of specialist support and intervention (Duff & Clarke, 2011).…”
mentioning
confidence: 99%
“…However, the prevalence of either type of deficit may differ within a particular dyslexic population. For example, Saksida et al (2016) showed that pure phonological deficits associated with dyslexia were actually much more frequent than pure visual attention span disorders in a French child population. However, Bosse et al (2007) found relatively equal proportions of the two dyslexic types in French and British groups of children.…”
Section: Reading Subskills: Auditory Phonology and Visual Attention Spanmentioning
confidence: 99%
“…To mention just a few, it has been argued that it is "widely agreed that developmental dyslexia is caused by a 'phonological core deficit'" (e.g. Goswami, 2003; and many others, see also Blomert, 2011;Olulade, Napoliello, & Eden, 2013;Saksida et al, 2016;Vellutino, Fletcher, Snowling, & Scanlon, 2004;Wimmer & Schurz, 2010, for recent discussions); that dyslexia is "a deficit in visuospatial attention, not in phonological processing" (Vidyasagar & Pammer, 2010); that "it is illogical to conclude that absence of evidence for some aspects of a magnocellular deficit in some dyslexics is evidence of its absence in all" (Stein, Talcott, & Walsh, 2000); that phonological and magnocellular deficit accounts both fail "to account for the full range of deficits established for dyslexic children … the full range of deficits might be accounted for in terms of a cerebellar deficit" (Nicolson, Fawcett, & Dean, 2001); and that "the cerebellum might stand unfairly accused, an innocent bystander in the processes responsible for disordered motor control in developmental dyslexia … the 'cerebellar' signs and symptoms associated with developmental dyslexia reflect a remote effect of neocortical perisylvian damage on cerebellar function" (Zeffiro & Eden, 2001). It has even been suggested that developmental dyslexia and specific language impairment are points on a continuum of learning disorders rather than distinct disabilities (Kamhi & Catts, 1986;cf.…”
Section: Introductionmentioning
confidence: 99%